The metabolites from traditional Chinese medicine targeting ferroptosis for cancer therapy - Tang, Yu; Zhuang, Ying; Zhao, Chuanxiang; Gu, Shuangshuang; Zhang, Junya; Bi, Shiqi; Wang, Ming; Bao, Lei; Li, Mei; Zhang, Wei; Zhu, Liqun (Frontiers in Pharmacology, 2024)
Cancer has emerged as a major disease with increasing morbidity and mortality year by year. The metabolites derived from traditional Chinese medicine (TCM) have played a significant role in combating cancers with curative efficacy and unique advantages. Ferroptosis, an iron-dependent programmed death characterized by the accumulation of lipid peroxide, stands out from the conventional cell death forms (such as apoptosis, pyroptosis, necrosis and autophagy). Recently, accumulating evidence has demonstrated the potential of TCM metabolites targeting ferroptosis for cancer therapy. We collected and screened the related papers up to June 2023 using PubMed, Google Scholar and Web of Science. The searched keywords in scientific databases were ferroptosis, cancer, tumor, traditional Chinese medicine, botanical drugs and phytomedicine. Only on research related to ferroptosis, the metabolites from traditional Chinese, and cancer will be considered. In this review, we introduced an overview of the current knowledge regarding the ferroptosis mechanisms and reviewed the research advances on the metabolites of TCM inhibiting cancer by targeting ferroptosis.